2001
DOI: 10.1046/j.1440-6055.2001.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Pest risk assessment of insects in sea cargo containers

Abstract: A survey of the floors of 3001 empty sea cargo containers in storage was undertaken to estimate the quarantine risk of importing exotic insect pests into Australia, with special reference to pests of timber. More than 7400 live and dead insects were collected from 1174 containers. No live infestations of timber‐feeding insects were recorded, but feeding damage detected in one floor indicates a low risk of importing colonies of timber pests in containers. The survey collection of dead insects demonstrates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 6 publications
0
59
0
1
Order By: Relevance
“…Given the rapid increase in shipping international cargo inside containers, which are seldom opened until they reach their final destination, there will likely be a shift in the locations where exotic insects first become established from near ports of entry to distribution centers throughout the country. Stanaway et al (2001) found insects, both dead and alive, in 39% of 3001 shipping containers that were inspected in Australia.…”
Section: Continentmentioning
confidence: 99%
“…Given the rapid increase in shipping international cargo inside containers, which are seldom opened until they reach their final destination, there will likely be a shift in the locations where exotic insects first become established from near ports of entry to distribution centers throughout the country. Stanaway et al (2001) found insects, both dead and alive, in 39% of 3001 shipping containers that were inspected in Australia.…”
Section: Continentmentioning
confidence: 99%
“…1 The cumulative number of identified insect species has increased steadily since 1820, a pattern that has been attributed to growth in international trade (Dehnen-Schmutz et al; Elton;Frey;Levine and D'Antonio;Maki and Galatowitsch;Niemela and Mattson;Perrings et al;Sailer 1978Sailer , 1983Stanaway et al;Weigle et al) and travel (Johnson, Ricciardi, and Carlton; Liebhold et al; Office of Technology Assessment) and natural habitat destruction (Pimentel, 1993;Taylor and Irwin;Vilà and Pujadas). Early introductions have been associated with European migration (Smith; Wheeler and Hoebeke), the surge in animal and plant imports following the founding of the U.S. Department of Agriculture (USDA) (Sailer, 1983), and large-scale commercial production of homogeneous crops and livestock (Capinera).…”
mentioning
confidence: 99%
“…As this work was not vector-or species-specific, for simplicity it was assumed that the probability of surviving transport ̿ is constant for all routes (Table 2) and estimates for this parameter were taken from Stanaway et al (2001). Estimates of the probability of establishment failure ̅ were based on the assumption that of the total number of species introduced to the recipient country the proportion that are establishment failures will be constant (0.98 based on estimates from di Castri, 1989).…”
Section: Modelmentioning
confidence: 99%
“…Consequently, only a small proportion of the potential vectors can actually be inspected McCullough et al, 2006) and a large number of organisms go undetected (Stanaway et al, 2001;Work et al, 2005). Inspection services also often only target agricultural pests, neglecting organisms that will have environmental impacts .…”
Section: Introductionmentioning
confidence: 99%